Spatial and temporal mangrove litter production in Barra de Navidad lagoon, Jalisco, México - Mendoza-Morales, Alma J. (2016)
Barra de Navidad lagoon is a coastal wetland of international importance (Ramsar site) and it is included among the 81 Mexican mangrove priority sites. One of the most valued characteristics of this lagoon is the presence of mangrove forest in a good conservation state. The goal of our research was the measurement of mangrove litter production and environmental factors influencing its dynamics. The mangrove area was divided into seven zones and litterfall was monthly sampled from November 2011 to October 2012 using 0.25 m2 square collectors made with mosquito mesh (1 mm) and positioned at 1.3 m above the ground. Abiotic variables of the interstitial water were measured simultaneously at each zone in permanent plots using a multi-parameter probe, YSI-556-M. Total mean value of litterfall production, weighted by zone surface, was 19.12 ± 1.23 gPS/m2.mo (2.29 t/ha.year). This low productivity is a consequence of the region’s dry climate and low tide range. The species Avicennia germinans and Laguncularia racemosa produced more than 80 % of total litterfall, while Rhizophora mangle contributed only 16 % and Conocarpus erectus < 4 %. A significant correlation between litterfall production and abiotic variables was found (e.g. salinity and interstitial water depth). We concluded that there are significant spatial variations in soil abiotic variables which are correlated with differences in mangrove species composition, and produce, together with the life cycles stages of those species, significant variations in the quantity and composition of litterfall. Future research will be focused on quantifying spatial variations in forest structure and their relationship with litterfall production.